2007
DOI: 10.1890/06-0078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of River Otter Activity on Terrestrial Plants in Trophically Altered Yellowstone Lake

Abstract: Animals that deposit aquatically derived nutrients on terrestrial landscapes link food webs and affect a variety of in situ processes. This phenomenon, however, is poorly documented in freshwater habitats, especially where species introductions have drastically changed an ecosystem's trophic structure. In this study, we used stable isotopes to document water-to-land nutrient transport by river otters (Lontra canadensis) around Yellowstone Lake, an ecosystem recently altered by nonnative species invasions. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 71 publications
(126 reference statements)
3
36
0
1
Order By: Relevance
“…First, our observed site-specific habitat measurements have shown that when establishing a latrine in all river reaches, river otters selected for similar features, namely high overstory and grass cover, moderately sloping banks, and relatively deep pools. These features have been previously described as suitable for river otters in western streams and lakes (Crait and Ben-David, 2007;DePue and Ben-David, 2010). As indicated by our habitat modeling, the NF had the highest availability of overstory and grass cover at the landscape level compared with the other two reaches.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…First, our observed site-specific habitat measurements have shown that when establishing a latrine in all river reaches, river otters selected for similar features, namely high overstory and grass cover, moderately sloping banks, and relatively deep pools. These features have been previously described as suitable for river otters in western streams and lakes (Crait and Ben-David, 2007;DePue and Ben-David, 2010). As indicated by our habitat modeling, the NF had the highest availability of overstory and grass cover at the landscape level compared with the other two reaches.…”
Section: Discussionsupporting
confidence: 69%
“…Errors using the TEV method were generally higher, but showed similar trends (Table B1). These error rates are higher than other studies in this region (Hayes et al, 2014), but adequate for quantification of habitat features important for river otters (i.e., overstory cover; Crait and Ben-David, 2007;DePue and Ben-David, 2010).…”
Section: Habitat Prey Availability and Disturbancementioning
confidence: 65%
“…Less often has this debate addressed the consequences of mitigating biological invasions in one ecosystem on linked ecological processes in an adjacent one. For example, river otters transfer aquatically-derived nutrients to terrestrial habitats via their scent-marking behavior at latrines and create "hot spots" of nutrient heterogeneity at the waterland interface (Ben-David et al, 2005;Crait and Ben-David, 2007;Roe et al, 2010). Our finding of behavioral changes in latrine use suggests that the spatial distribution of these hot spots may have shifted away from tributary streams.…”
Section: Implications For Conservation Of Aquatic-terrestrial Linkagementioning
confidence: 79%
“…Several studies in temperate forests have shown increased nitrogen (N) concentration in plant tissue or increased plant production in response to such animal-mediated nutrient transfers (Ben-David et al 1998a, b, Hilderbrand et al 1999, Helfield and Naiman 2001, 2002, Crait and Ben-David 2007.…”
Section: Introductionmentioning
confidence: 99%